New RuII(arene) complexes with halogen-substituted bis- and tris(pyrazol-1-YL)borate ligands - Orbisaglia, Serena (2015)
[RuCl(arene)(-Cl)](2) dimers were treated in a 1:2 molar ratio with sodium or thallium salts of bis- and tris(pyrazolyl)borate ligands [Na(BpBr3)], [Tl(TpBr3)], and [Tl(Tp(iPr,4Br))]. Mononuclear neutral complexes [RuCl(arene)((2)-BpBr3)] (1: arene=p-cymene (cym); 2: arene=hexamethylbenzene (hmb); 3: arene=benzene (bz)), [RuCl(arene)((2)-TpBr3)] (4: arene=cym; 6: arene=bz), and [RuCl(arene)((2)-Tp(iPr,4Br))] (7: arene=cym, 8: arene=hmb, 9: arene=bz) have been always obtained with the exception of the ionic [Ru-2(hmb)(2)(-Cl)(3)][TpBr3] (5), which formed independently of the ratio of reactants and reaction conditions employed. The ionic [Ru(CH3OH)(cym)((2)-BpBr3)][X] (10: X=PF6, 12: X=O3SCF3) and the neutral [Ru(O2CCF3)(cym)((2)-BpBr3)] (11) have been obtained by a metathesis reaction with corresponding silver salts. All complexes 1-12 have been characterized by analytical and spectroscopic data (IR, ESI-MS, H-1 and (CNMR)-C-13 spectroscopy). The structures of the thallium and calcium derivatives of ligand TpBr3, [Tl(TpBr3)] and [Ca(dmso)(6)][TpBr3](2)2DMSO, of the complexes 1, 4, 5, 6, 11, and of the decomposition product [RuCl(cym)(Hpz(iPr,4Br))(2)][Cl] (7) have been confirmed by using single-crystal X-ray diffraction. Electrochemical studies showed that 1-9 and 11 undergo a single-electron (RuRuIII)-Ru-II oxidation at a potential, measured by cyclic voltammetry, which allows comparison of the electron-donor characters of the bis- and tris(pyrazol-1-yl)borate and arene ligands, and to estimate, for the first time, the values of the Lever E-L ligand parameter for BpBr3, TpBr3, and Tp(iPr,4Br). Theoretical calculations at the DFT level indicated that both oxidation and reduction of the Ru complexes under study are mostly metal-centered with some involvement of the chloride ligand in the former case, and also demonstrated that the experimental isolation of the (3)-binuclear complex 5 (instead of the mononuclear 5) is accounted for by the low thermodynamic stability of the latter species due to steric reasons.